O48 PREOPERATIVE CT IMAGING IN PATIENTS WITH STRANGULATED ABDOMINAL WALL HERNIAS DELAYS SURGERY AND INCREASE RISK OF BOWEL RESECTION: A RETROSPECTIVE RECORD BASED STUDY. (25th November 2021) - Ibrahim, Walid; Magee, Conor; Wilson, Jeremy
Abstract: Aim: "To investigate whether preoperative CT imaging in acute symptomatic hernia was associated with either surgical delays or increase risks of bowel ischemia and the need for resection." Material and Methods: "The data was collected retrospectively for patients who had emergency hernia surgeries in the period between June 2003 till January 2021. We studied the role of preoperative CT scan in delaying surgical intervention and its impaction on intra-operative surgical intervention, postoperative complication, HDU admission and hospital length of stay." Results: "Data analysis was performed for 505 patients, 191 had preoperative CT scan. Hernia types included inguinal in 164 patients (32.5%); umbilical in 164 (32.5%); femoral in 69 (13.7%); incisional in 69 (13.7%); epigastric in 30 (5.9%); Spigelian in 9 (1.8%). Preoperative CT scan was associated with surgery delay (22.0 hours vs 13.0 hours, P 9.77e-16). Delayed surgery had an impact on increasing postoperative complications (5.2% vs 3.5%, P 0.4741), longer mean postoperative hospital lengths of stay (9.23 days vs 5.12 days, P 2.2e-16), and increase HDU admission (11.0% vs 4.8%, P 0.01408). Increase bowel resection (12% vs 6.4%, P 0.04032) with surgery delay (20.0 hours vs 12.0 hours, P 0.003448) and also increase omentum resection (7.3% vs 5.4%, P 0.4974) with surgery delay (22.5 hours vs 13.5 hours, P 0.02083) were noted." Conclusions: "Pre-operative CT scan for emergent hernias leads to delay in surgical intervention. Surgery delay leads to more aggressive intra-operative intervention and worse postoperative outcomes."